UTILIZATION OF 1% OF METHYLENE BLUE IN STAINING HISTOPATHOLOGICAL PREPARATIONS AT ANATOMIC PATHOLOGY LABORATORY - Tri Rahmawati; Yadi Apriyadi; Mamay (Universitas Nahdlatul Ulama Surabaya, 2020)
Tissue staining using hematoxylin-eosin (HE) is a standard method of histopathological staining. The tissue staining is hampered when there is no hematoxylin reagent in laboratory. Therefore, other reagents are needed that can replace the use of hematoxylin. Methylene blue is a basic dyes that interact with cell nuclei which has a negative ionic charge of the tissue. It can be used as an alternative nuclei staining. This study aims to evaluate the use of 1% of methylene blue in cell nuclei staining in histopathological preparations. The research sample were 15 pathology preparations which were randomly selected including breast cancer, cervical cancer and ovarian cancer in the bank of sampel at anatomical pathology laboratory of RSUD Dr. Slamet Garut, Indonesia. The experiment showed that the methylene blue dyes yielded “worth” result (40%) and “poorly” result (60%). Further research can be carried out by modifying the pH of 1% of methylene blue reagent so that it can maximize the staining preparations results as good as those using hematoxylin.